1969
DOI: 10.1017/s0022029900012577
|View full text |Cite
|
Sign up to set email alerts
|

Lactose, lactic acid and mineral equilibria in Cheddar cheese manufacture

Abstract: SummaryIn experimental small-scale manufacture of Cheddar cheese a study was made of the movement of lactose, lactic acid, calcium and phosphorus between curd and whey, and of the effect of high acidity developed in the curd before whey separation, on the pH and physical properties of the cheese. It was found that while the curd particles remain in contact with the whey, the lactose fermented in the curd is replaced by lactose diffusing from the whey. Lactic acid produced in the curd diffuses into the whey rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
(4 reference statements)
5
22
0
3
Order By: Relevance
“…As discussed below, the pH after brining was significantly lower in the cheeses cooked to 47 1C than in those cooked to 50 or 53 1C. This lower pH may have increased the degree of solubilisation of micellar calcium phosphate (Van Hooydonk, Hagedoorn, & Boerrigter, 1986) permitting increased soluble calcium to be lost from the curds during whey drainage (Czulak, Conochie, Sutherland, & van Leeuwen, 1969).…”
Section: Cheese Compositionmentioning
confidence: 96%
“…As discussed below, the pH after brining was significantly lower in the cheeses cooked to 47 1C than in those cooked to 50 or 53 1C. This lower pH may have increased the degree of solubilisation of micellar calcium phosphate (Van Hooydonk, Hagedoorn, & Boerrigter, 1986) permitting increased soluble calcium to be lost from the curds during whey drainage (Czulak, Conochie, Sutherland, & van Leeuwen, 1969).…”
Section: Cheese Compositionmentioning
confidence: 96%
“…However, the pH at 2 d of the MSC cheeses was similar to that of the ST cheeses and significantly higher than that of the SC cheeses. These significant differences between the SC and MSC were attributed to the use of a curd-washing step during manufacture, which reduced lactose content and regulated acidification (Czulak et al, 1969;Huffman & Kristoffersen, 1984;Shakeel-Ur-Rehman et al, 2004). There was no significant difference at 2 d between the pH of the MST and SC cheeses, however the pH of the ST cheeses was higher than that of the MST cheeses.…”
Section: Compositionmentioning
confidence: 99%
“…Cheese pH controls the rate of growth and metabolism of PAB (Kurtz, Hupfer, Corbin, Hargrove, & Walter, 1959;Turner, Morris, & Martley, 1983) and a higher inocula is required for cheeses with a lower cheese pH (Frö hlich-Wyder & Bachmann, 2004). Curd washing enables regulation of acid production and thus pH during cheese manufacture and ripening (Czulak, Conochie, Sutherland, & van Leeuwen, 1969;Huffman & Kristoffersen, 1984;Shakeel-UrRehman, Waldron, & Fox, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, analysis of data from previous studies (Czulak, Conochie, Sutherland, & van Leeuwen, 1969;Guinee, Kilcawley, & Beresford, 2008;Huffman & Kristoffersen, 1984;Martley & Crow, 1993;Rynne et al, 2007;Turner & Thomas, 1980) indicated that the reported concentrations of LLAMc (3.4e4.6%, w/w) for Cheddar cheese are lower than those expected (w4.3e5.2%, w/w) based on the seasonal variations in the concentration of lactose milk of (w4.0e4.8%, w/w) (O'Brien et al, 1999). The lower levels of LLAMc compared with that of LIMm may reflect a more rapid diffusion rate of lactic acid from the moisture phase of the curd particle (where lactose is being fermented to lactic acid by the starter culture) than that of lactose from the whey into curd particle because of the lower molecular mass of the former compared with the latter (w90 and 342 Da, respectively) and the higher concentration of lactate in the curd particle moisture.…”
mentioning
confidence: 98%